أثر الصلح في سقوط العقوبة - فاروق محفوظي; نورالدين العربي (جامعة عمار ثليجي الاغواط, 2023)
الشريعة الإسلبمية رسالة إصلبح كىداية ,كضعت منياجا لبناء المجتمع كحمايتو كتحصينو مف كؿ ما يزعزع استق ا رره , فشرعت كؿ ما يحتاجو الفرد كالمجتمع مف أحكا كمبادئ كقي . كلإصلبح المجتمع كحمايتو, شرع الإسلب العقكبات حماية لأف ا رده مف ضياع أمكالي أك أع ا رضي , كحفاظا عمى ت ا ربط الجماعة كانتشار الأمف , فالإسلب بمنيجو الفريد المعجز أكجد مجتمعات تقؿ فييا الجريمة ,تقؿ فييا فرص تنفيذىا , كما شرع العقكبات شرع في المقابؿ أسبابا تسقط ىذه العقكبات ,كمف أجؿّ ىذه الأسباب نجد الصمح. فالصمح بيف الناس خير.., تسكف بو النفكس ,كيتلبشى الن ا زع , كيزكؿ الحقد . كىك نيج شرعي يصاف بو الإنساف كتحفظ بو المجتمعات مف الخصا كالشقاؽ ك التفكؾ. كبو تعمر البيكت ,كينتشر الأمف كالاستق ا رر بيف أف ا رد المجتمع , كمف ث يتفرغ الناس للؤعماؿ الصالحة ,,كيتفرغكف لمبناء ك الإعمار بدلا مف إفناء الشيكر كالسنكات في المنازعات كالخصكمات ك إ ا رقة الدماء كتبديد الأمكاؿ ,فالإسلب قرر أف الصمح خير ، فجاء بحثنا ليعالج مكضكع أثر الصمح في سقكط العقكبة ,كقد تطرقنا إليو لنب يّف مفيك الصمح كمشركعيتو كنكضح مفيك العقكبة كأقساميا كما يسقط منيا بالصمح . كب ينا أف الصمح لو أثر في سقكط العقكبة التي ىي حؽ لمعباد) حؽ الآدمي ( كىي أنكاع عقكبات القصاص حد القذؼ عند مف يقكؿ بأنو حؽ لممقذكؼ ك عقكبات التعزير الكاجب للآدمي. - أكنو ليس لمصمح أثر في سقكط العقكبة التي ىي حؽ لله مثؿ الحدكد. قاؿ الشيخ الطاىر بف عاشكر) السماحة أكؿ أكصاؼ الشريعة ك أكبر مقاصدىا (. كالشريعة الإسلبمية لا تشمؿ في نصكص منيا عمى نكاية بالإنساف أك بالأمة الإسلبمية . كاستق ا رء نصكص الشريعة دؿّ عمى أف السماحة كالصمح كاليسر مف مقاصد الديف . الكممات المفتاحية: الصمح , سقوط , العقوبة. - 103 - Summary The lslamic Sharia is a message of reform and guidance that set a platform for building society ,protecting it and fortifying it from everything that destabilizes its stability , so it legislated all that the individual and society needs in terms of provisions , principles and values to reform society and protect it ,lslam prescribed unishments to protect its member from the loss of their money and honor , and to preserve the cohesion of the group and the spread of security . lslam with its unique and miraculous approach , has created societies in which crime is reduced and the chances of its execution are reduced . we have legislated punishments , and in return ,it has legislated reasons for these punishments to fall ,and one of the greatest of these reasons is conciliation . Reconciliation between people is a good in which souls calm down ,conflict fades away ,and hatred disappears .lt is a legitimate approach by which people are protected and societies are preserved from strife ,discord and disintegration . With reconciliation ,homes are rebuilt , security and stability spread among the members of society , and then people devote themselves to good deeds and devote themselves to building and reconstruction instead of spending months and years in disputes ,rivalries , bloodshed , and squandering money .so , lslam decided that reconciliation is good Thus ,our research highlights the effect of conciliation on the fall of punishment .We clarified the concept of conciliation and its legitimacy , the concept of punishment and its divisions and the punishment that falls by conciliation ,and we can summarize it that reconciliation has an impact on the fall of the punishment [which is a right for the servants].However ,it has no effect on the fall f punishment , which is a right of God. - 104 - Sheikh Taher bin Ashour said :[forgiveness is the first description of the Sharia and its greatest purpose].The lslamic nation And the extrapolation of the law indicates that forgiveness , peace and ease are among the purposes of religion .
د/امحمد علالي